Colloid electrochemistry of conducting polymer: towards potential-induced in-situ drug release. (20th February 2017) - Sankoh, Supannee; Vagin, Mikhail Yu.; Sekretaryova, Alina N.; Thavarungkul, Panote; Kanatharana, Proespichaya; Mak, Wing Cheung
Graphical abstract: Highlights: Pulsed electrode potential induced an in-situ drug release from dispersion of conducting polymer microcapsules. Fast detection of the released drug within the colloid microenvironment. Improved the efficiency of localized drug release at the electrode interface. Abstract: Over the past decades, controlled drug delivery system remains as one of the most important area in medicine for various diseases. We have developed a new electrochemically controlled drug release system by combining colloid electrochemistry and electro-responsive microcapsules. The pulsed electrode potential modulation led to the appearance of two processes available for the time-resolved registration in colloid microenvironment: change of the electronic charge of microparticles (from 0.5 ms to 0.1 s) followed by the drug release associated with ionic equilibration (1–10 s). The dynamic electrochemical measurements allow the distinction of drug release associated with ionic relaxation and the change of electronic charge of conducting polymer colloid microparticles. The amount of released drug (methylene blue) could be controlled by modulating the applied potential. Our study demonstrated a surface-potential driven controlled drug release of dispersion of conducting polymer carrier at the electrode interfaces, while the bulk colloids dispersion away from the electrode remains as a reservoir to improve the efficiency of localized drug release. The developed new methodology creates a model platform for the investigations of surface potential-induced in-situ electrochemical drug release mechanism.